Game Form Misconceptions Do Not Explain the Endowment Effect - Björn Bartling; Florian Engl; Roberto A. Weber (Center for Economic Studies and ifo Institute (CESifo), 2014)
We test the claim that game form misconception among subjects making choices through the Becker-DeGroot-Marschak (BDM) value elicitation procedure provides an explanation for the endowment effect, as suggested by Cason and Plott (forthcoming). We employ a design that allows us to clearly identify whether subjects comprehend the incentive properties of a price-list version of the BDM procedure. We find a robust endowment effect, even among those subjects whose elicited valuations for a known monetary value and whose ability to calculate the payoffs resulting from their choices indicate no misconception of the task. We conclude that game form misconceptions alone are unlikely to account for behavioral patterns like the endowment effect.
Keywords: C91; D03; 330; endowment effect; game form misconception; BDM mechanism; experimental methods; replicable audio files of instructions